1989
DOI: 10.1007/bf02554501
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of direct spread in Dukes' C cases of rectal cancer

Abstract: Seventy-six cancers with involved lymph nodes but with limitation of direct spread in continuity to the bowel wall (Astler-Coller C1 cases) were matched with Astler-Coller C2 cases for clinical variables, macroscopic appearance of tumor, grade of differentiation, and number of positive lymph nodes. Despite this stringent matching, spread was shown to be an important prognostic variable in univariate survival analysis. Estimated five-year survival for Astler-Coller C1 cases was just below 80 percent, equivalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 11 publications
1
22
0
1
Order By: Relevance
“…In one study using univariate analysis, cal node will vary with the extent of surgery. '6,21,the number of peripheral nodes involved was not significantly related to prognosis, and node level was shown to be of prime imp~rtance. '~ In contrast, using a different definition of node level, Wolmark et aLZ8 found that the level of node involvement contributed little additional information to that provided by the number of involved nodes and the depth of tumor penetration.…”
Section: Discussionmentioning
confidence: 92%
“…In one study using univariate analysis, cal node will vary with the extent of surgery. '6,21,the number of peripheral nodes involved was not significantly related to prognosis, and node level was shown to be of prime imp~rtance. '~ In contrast, using a different definition of node level, Wolmark et aLZ8 found that the level of node involvement contributed little additional information to that provided by the number of involved nodes and the depth of tumor penetration.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, the diagnosis of rectal cancer is usually made on the basis of a rectal digital examination, sigmoidoscopy or colonoscopy, a double contrast enema examination, and confirmatory histologic findings (10). However, these approaches do not adequately show the depth of tumor spread or the extent of lymph node involvement, both of which are important prognostic features (11)(12)(13)(14)(15). Preoperative staging techniques for rectal cancer should allow identification of (a) patients with extrarectal spread, who might benefit from preoperative radiation therapy; and (b) patients with minimal or no sphincteral involvement, who might be suitable for sphincter-sparing surgery.…”
Section: Rectal Cancermentioning
confidence: 99%
“…The presence and number of involved lymph nodes are strongly related to survival and local recurrence rates. [1][2][3][4][5][6] Currently, postoperative histopathologic examination of resected colorectal lymphatic tissues is the standard means of assessing lymph node status for staging. Although CT and MRI have been investigated as preoperative methods for assessment of lymph node metastasis, these imaging methods do not distinguish between metastatic and nonmetastatic lymph nodes with sufficient accuracy: the sensitivities of both tests are low, although the specificities are high.…”
Section: Received 11 July 2002; Accepted 4 June 2003mentioning
confidence: 99%